2021
DOI: 10.1017/s0033291721000040
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the genetic and environmental aetiologies of non-suicidal and suicidal self-harm: a twin study

Abstract: Background Self-harm is a major health concern, not only as a signal of distress but also as a strong predictor of later suicide. Self-harm can be further refined into suicidal self-harm (SSH, i.e. suicide attempt) and non-suicidal self-harm (NSSH). Understanding the aetiologies of NSSH and SSH can help inform suicide prevention strategies. Using a twin design, we investigated the phenotypic and aetiological relationships between NSSH and SSH, and their aetiological overlap with mental health problems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Furthermore, in sensitivity analyses, we found no marked differences in risk factors for near-lethal suicide attempts and suicide attempts more generally. Collectively, these findings may reflect a shared vulnerability to self-harm irrespective of intent or lethality (Lim et al, 2021;Mars et al, 2014a), although future longitudinal studies that directly compare risk factors for multiple outcomes in the same prison population are needed to clarify this. This review highlights several modifiable factors that can be targeted by interventions and may improve suicide prevention in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in sensitivity analyses, we found no marked differences in risk factors for near-lethal suicide attempts and suicide attempts more generally. Collectively, these findings may reflect a shared vulnerability to self-harm irrespective of intent or lethality (Lim et al, 2021;Mars et al, 2014a), although future longitudinal studies that directly compare risk factors for multiple outcomes in the same prison population are needed to clarify this. This review highlights several modifiable factors that can be targeted by interventions and may improve suicide prevention in prisons.…”
Section: Discussionmentioning
confidence: 99%
“…Using the classical twin design, Lim et al ( 2021) found strong phenotypic (r = 0.87) and genetic (r g = 0.94) correlations between NSSH and SSH; and that the genetic and environmental relationships of 17 mental health measures with NSSH were comparable to those with SSH. In that twin study, major depressive disorder (MDD) symptoms and insomnia were identified to have the strongest phenotypic and genetic correlations with both NSSH and SSH among 17 mental health measures (Lim et al 2021). This was also supported by two recent molecular genetic studies, where MDD and insomnia had significant…”
mentioning
confidence: 64%
“…By estimating only C x , rC and Cy are constrained to zero by default (see Minică et al, [2018], Scenario 6 in Table 1). Based on earlier research using the same sample that showed that depression and ADHD are ACE traits (Greven et al 2011;Waszczuk et al 2015Waszczuk et al , 2021 whereas NSSH and SSH are AE traits (Lim et al 2021), we initially adopted ACE models for the exposures and AE models for the outcomes, with rC and Cy constrained to zero by default. However, this model had a low resolution (i.e., the confidence intervals were extremely wide e.g., -37 to 477 for a causal path estimate of 0.66).…”
Section: Mental Health Measures (Exposure Variables)mentioning
confidence: 99%
“…Twin and family studies have been best able to answer these questions using distinct phenotypes; for example, a recent study from Kendler et al [32] found evidence to suggest that suicide attempt and death by suicide are genetically distinct in ways beyond severity. Still, some relationships between these phenotypes are less clear, with some twin studies having found that a large portion of the variation in suicide attempt is explained by genetic factors shared with nonsuicidal self-injury [33] and that the two behaviors share a genetic correlation of 0.94 [34], while a study from Russell et al [35] was not able to identify any genetic correlation between non-. CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Introductionmentioning
confidence: 99%
“…[32] found evidence to suggest that suicide attempt and death by suicide are genetically distinct in ways beyond severity. Still, some relationships between these phenotypes are less clear, with some twin studies having found that a large portion of the variation in suicide attempt is explained by genetic factors shared with non-suicidal self-injury [33] and that the two behaviors share a genetic correlation of 0.94 [34], while a study from Russell et al . [35] was not able to identify any genetic correlation between non-suicidal self-injury and suicide attempt, although in a considerably smaller sample.…”
Section: Introductionmentioning
confidence: 99%